2015
DOI: 10.1097/wno.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diabetes Mellitus on Giant Cell Arteritis

Abstract: Objective To determine if type 2 diabetes mellitus (DM) is protective against giant cell arteritis (GCA) and to estimate the incidence of GCA diagnosis in the Medicare population. Methods Medicare 5% claims files from 1991-2011 were used to identify beneficiaries diagnosed with DM, but not GCA, within a three-year ascertainment period. Propensity score matching was used to define a control group of non-diabetics with comparable demographic covariates. Competing-risk regression was then used to assess the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Other published studies, including a recent report using Medicare, claims file data have suggested that GCA occurs less commonly in African-American populations, including areas where the population is composed of significant numbers of African-Americans. 1,7,37,38 Our findings are consistent with these reports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other published studies, including a recent report using Medicare, claims file data have suggested that GCA occurs less commonly in African-American populations, including areas where the population is composed of significant numbers of African-Americans. 1,7,37,38 Our findings are consistent with these reports.…”
Section: Discussionsupporting
confidence: 92%
“…3 Since then a few studies have reported on the occurrence of GCA in minority groups. The incidence in African-Americans is believed to be lower than in Caucasians, 1,[4][5][6][7] but there is no clear consensus on the nature of disease presentation in this population, as the majority of studies of GCA in African-Americans are case reports or small case series. [8][9][10][11][12][13][14][15][16][17] One study did not find a difference in the presentation of GCA in African-Americans compared with Caucasians, 17 another reported higher rates of vision loss and jaw claudication, 15 and a third noted higher rates of male patients, vision loss, and anemia, and lower rates of constitutional symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Among the cases who subsequently developed GCA, not a single individual had a history of diabetes at baseline, compared with 2.3% of the controls. This is in line with studies suggesting that GCA cases at the time of diagnosis have a lower prevalence of diabetes compared with controls [ 12 ], although there are conflicting results [ 13 ]. Methodological differences in diabetes ascertainment and possibly age-related effects of diabetes on the risk of GCA may explain such discrepancies.…”
Section: Discussionsupporting
confidence: 90%
“…A meta-analysis of observational studies demonstrated that patients with GCA have a significantly reduced prevalence of diabetes at the time of diagnosis compared with the general population [ 12 ], but a subsequently published large register-based study came to the opposite conclusion [ 13 ]. It has been shown that during the first 2 years after GCA diagnosis, the incidence of diabetes is increased, most likely due to treatment with high doses of glucocorticoids [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since an optimal approach to identifying GCA using administrative data is unknown, we attempted to control for the misclassification of GCA by limiting eligible subjects to those >50 years of age and requiring at least 2 outpatient encounters with the diagnostic code or the inclusion on the hospital discharge form. Other investigators have used similar GCA definitions . In sensitivity analyses, we also made our GCA definition more specific in several ways: by requiring a CPT code for temporal artery biopsy, by requiring at least 2 steroid prescriptions, or by requiring at least 1 outpatient diagnostic code for GCA to have been assigned by a rheumatologist.…”
Section: Discussionmentioning
confidence: 99%